Epistemological Challenges of Hadith Authentication in the Digital Era: A ‎Philosophy of Science Perspective - Ilman Hendrawan Saputra; Achmad faiz fadhlurrahman fadily (Jurnal Ulunnuha, 2025)
This study aims to identify and analyze the forms of hadith dissemination through digital media, particularly websites, and to classify the types of websites that serve as a means of hadith study. This study is motivated by the lack of research that explicitly discusses the role of websites as a medium for the transmission and study of hadith in the digital age, even though previous studies have discussed software such as Lidwa, Maktabah Syamilah, and Gawāmi' al-Kalim. This research uses a descriptive qualitative approach based on literature study, with hermeneutics as a method to understand methodological transformations in hadith studies, as well as triangulation of sources by involving hadith experts and Islamic information technology practitioners to ensure cross-disciplinary validity. The human-in-the-loop principle is applied to integrate Islamic scientific values into the hadith digitization system. The results show that the dissemination of hadith through websites not only expands access to hadith literature but also raises new challenges in terms of the authority and authenticity of information. Websites are classified into several types, including: (1) hadith aggregator websites with search and sanad filter features, (2) hadith-based digital education platforms, and (3) AI-based hadith verification sites that function assistively. Thus, these findings confirm an epistemological renewal in the form of placing AI as a limited tool, not a substitute for human judgment.